EFFECTS OF RIDING THERAPY IN CHILDREN AND ADOLESCENTS WITH DOWN SYNDROME (Fiep Bulletin - online, 2025)
Introduction: The use of equine therapy as a therapeutic resource within physiotherapy has been growing recently. In this method, the horse becomes an agent that promotes physical, psychological, and educational gains. This resource can be used in different pathologies, especially Down syndrome, and intervenes in aspects such as postural control, stability, and balance. Objective: This research aimed to verify the effects on motor aspects of Hippotherapy in children and adolescents with Down syndrome. Methods: The research is quantitative and qualitative in nature and the sample includes children and adolescents with Down Syndrome aged five and fourteen who meet the inclusion terms of this study. Two children were monitored for a period of two months. The evaluation was biweekly and consisted of an assessment form, an anamnesis form, and a Motor Development Scale. Results: In the final assessment, the results were positive, showing improvements in the areas of balance, global motor skills, and spatial organization. Conclusion: There are benefits to the quality of life, well-being, and motor development of children and adolescents with Down Syndrome who practice hippotherapy.
Keywords: Equine-assisted therapy; Children; Motor development; Therapeutic riding